Kewarisan Anak di Luar Perkawinan di Tengah Isu Gender - Wahidah, Wahidah (IAIN Antasari Banjarmasin, 2013)
Child before of marriage is basicly a term which definition is rather difficult to be correlated with the term natural child (ibn al mulaanah) as stipulated in fiqh. This difficulty is triggered by the